IMPLEMENTASI LOGIKA FUZZY MAMDANI UNTUK MENENTUKAN KOMPOSISI OPTIMAL PUPUK ORGANIK DAN ANORGANIK NPK PADA TANAMAN MENTIMUN - Fajar Ridwan Analistyawan; Sutrisno Sutrisno; Solichin Zaki (Journal of Fundamental Mathematics and Applications (JFMA), 2018)
In this article, we have determined the optimal composition of organic fertilizer and NPK inorganic fertilizer for cucumber plants. We have formulated two fuzzy systems which are fuzzy system 1 and fuzzy system 2. The inputs for fuzzy system 1 are plants’ height and the number of leaves where the output is the growth rate. Fuzzy system 2 had input of growth rate and NPK concentration and output of organic fertilizer concentration. By processing the data using fuzzy system, we have compared the cucumber plant with organic fertilizer and NPK to cucumber plant that was used only NPK fertilizer. The result had shown that the cucumber plant with organic fertilizer and NPK was produced the better outcome than the cucumber plants with NPK only.